Speaking Learning Strategies of English Department Students at Sintuwu Maroso University - Ika Paramitha Lantu; Stevani Ernida Tindika (Sintuwu Maroso Journal of English Teaching, 2021)
This research aims to find out the speaking learning strategies used by the fourth semester students of the English Language Department at Sintuwu Maroso University. This research is a descriptive qualitative research that uses questionnaire, interview, and documentation to collect data. The subjects of this research are fourth semester students of the English Language Education Study Program in the 2020/2021 academic year that enrolled in the Academic Speaking class. The questionnaire was given to 20 students, and the interviewees are 6 students. The results show that the fourth semester students of the English Language Education study program have applied all strategies, they are: effective memorizing activity (memory strategy), using mental processes (cognitive strategy), compensating disappeared knowledge (compensation strategy), controlling and evaluating learning (metacognitive strategy), regulate emotions (affective strategy), and cooperate with others (social strategy).